Theoretical Study on Structures and Properties of High-Energy Density Derivatives of Pyridine - Lian, Peng; Lai, Wei-Peng; Wang, Bo-Zhou; Wang, Xi-Jie; Luo, Yi-Fen (Asian Journal of Chemistry, 2014)
The geometries of pyridine and its eight derivatives have been fully optimized at the level of B3LYP/6-31G**. The vibration frequencies, nature bond orbits and IR spectra have been calculated at the same level. The results show that the introduction of energetic groups, such as -NO and -C(NO2)3 will elongate the C-C bonds and shorten C-N bonds of pyridine rings at same time and the interaction of p orbit and the adjacent p* orbit can improve the stability of pyridine ring. The stretching vibration bands of pyridine rings show bathochromic shift after the groups introduced as the result of conjugation effect. Their density, detonation velocity and detonation pressure are predicted, and the results show they are high-energy-density compounds. The properties are proportional to number of -NO2 or -NO in the ring.